Pengaruh Good Corporate Governance Dan Budaya Organisasi Terhadap Kinerja Lembaga Perkreditan Desa (LPD) Dengan Kompetensi Manajerial Sebagai Variabel Moderasi Pada LPD Se-Kecamatan Penebel - Ni Wayan Siska Yanti; Ni Wayan Alit Erlina Wati; Putu Nuniek Hutnaleontina (UNHI Press, 2023)
Organizational performance (LPD) is the work result of various goals that have been planned beforehand, and is used as a benchmark in organizational assessment. Evaluation is carried out to determine the effectiveness and efficiency of LPD activities in achieving the goal of developing a business. This research was conducted in order to determine the effect of Good Corporate Governance and Organizational Culture on the Performance of Village Credit Institutions (LPD) with Managerial Competence as a Moderating Variable in LPDs throughout Penebel District. The population in this study amounted to 170 respondents consisting of the Chairperson, Secretary and Treasurer of the LPD in 58 LPDs throughout Penebel District. The sample in this study amounted to 170 people who were determined by saturation sampling technique and tested by Partial Least Squares analysis technique. The results of this study explain that Good Corporate Governance and Organizational Culture have a positive and significant influence on the Performance of Village Credit Institutions. Meanwhile, the interaction between Managerial Competence and Good Corporate Governance and Organizational Culture has a positive and insignificant influence on the Performance of Village Credit Institutions.